Theorizing Queer from the Americas - Schramm, Christina (2017)
In this article I suggest a queer theorizing from the Americas that articulates itself from its own margins. By referring to Judith Butler’s philosophical thought and to the 5th International Conference Queer Paradigms in Quito, Ecuador, I discuss constructions of sexuality and gender in relation to the State and the (un) belonging to the nation. Particularly I bring up migration, Indigeneity and Blackness to problematize some of the possible multiple discriminations. This emphasis on multidimensionality is central in queering knowledge production both, theoretically and politically.